Message Design Matters: An Experiment on Portrayal of Protective Action Guidance in Warning Messages for Three Hazards - Ginger Orton; Laura Morgan Fischer; Jeannette Sutton; David Huntsman (Journal of Applied Communications, 2025)
Risk communicators play a crucial role in informing individuals about approaching hazards and guiding them on how to respond effectively during different phases of disaster communication. Protective action guidance has been defined as the information people need to inform them of what to do to protect themselves in the face of a hazardous situation. However, many social media messages disseminated by the National Weather Service do not include protective action guidance. Scholars have called for more research on the portrayal of protective action guidance in a message to prove which design best imparts protective action knowledge. To answer this call, a researcher-developed conceptual framework was used to explore how four portrayals of protective action guidance influence knowledge of protective actions (i.e., protective action literacy). We first describe individuals' perceptions of the appropriate protective actions to take when either a dust storm, snow squall, or tornado is approaching. Then, we report on changes in protective action literacy after exposure to a series of hazard warning messages with varying portrayals of protective action guidance. The study's results reveal important insights regarding the influence of protective action guidance portrayal in warning messages on participants’ protective action literacy. Participants' understanding of appropriate protective actions varied across hazards and was influenced by message type. This research highlights the importance of evidence-based message design, the need for comprehensive guidance for all hazards, and the role of agricultural communication in disaster preparedness. The study's findings can inform more effective disaster communication strategies and guide future research.
Keywords: Hazard communication; message design; protective action guidance; weather alerts; snow squall; tornado; dust storm